印尼泗水黄龙体育会龙狮队的发展研究 - Olivia Olivia; ShuiQing Zhu (Ma Chung Press, 2022)
【摘要】舞狮是源自中国的一种民间艺术活动，其形成经历了漫长的历史过程，慢慢成为了一种独特的中国传统文化。这种文化在中国得到广泛的传播，后随着华人移民到世界各地，舞狮活动也被带入，可以说是有华人的地方就有舞狮。而印度尼西亚作为一个拥有大量华人移民的国家，舞狮活动也在本国传播，舞狮活动在传播中结合吸收了当地的文化，有自己的特色，成为了印尼文化的组成部分。本文以泗水黄龙体育会舞狮团队研究对象，采用了访谈和文献研究方法，从舞狮的起源、表演动作、表演流程等对其进行了研究。研究表明：黄龙体育会舞狮团队自1978年成立到现在，经历了“新持序”时期，宗教改革，舞狮队从队员血统、舞狮仪式、训练方法到舞狮的功能都发生了很大的变化。 【关键词】舞狮，民间活动，黄龙体育会舞狮团队，印尼，泗水 Abstract The lion dance is a kind of folk art activity originated from China. Its formation has gone through a long historical process and has gradually become a unique Chinese traditional culture. This kind of culture has been widely spread in China. Later, as Chinese emigrated to all over the world, lion dance activities were also brought in. It can be said that there is lion dance where there are Chinese. As a country with a large number of Chinese immigrants in Indonesia, lion dance activities are also spread in the country. The lion dance activities incorporate local culture in the spread, have their own characteristics, and become an integral part of Indonesian culture. This article uses the research object of the lion dance team of the “Surya Naga” Sports Club in Surabaya, using interviews and literature research methods to study the lion dance's origin, performance, and performance process. Studies have shown that since the establishment of the Lion Dance Team of the “Surya Naga” Sports Club in 1978, it has gone through the